JANGER BANYUWANGI DAN MENAKJINGGO: REVITALISASI BUDAYA - Novi Anoegrajekti (Faculty of Humanities, Jember University, 2014)
This study emphasizes how an identity has been built in its contact with modernization. This is evident in the changes in the Janger text of Banyuwangi. As a cultural event, the Banyuwangi Janger art performance is unique because it is a hybrid, which is a combination of art which originated from Banyuwangi, Java, and Bali. Costumes, dances, and musical instruments are similar to Bali. As an ethnographic study, the Using people of Banyuwangi perceive and respond to the Janger art performance as a continously changing identity construction. Keywords: identity, janger, modernization